Еffects of i group metals nitrates on parameters of multibilayer lipid membranes - Vashchenko, O. V. (Biophysical Bulletin)
Effects caused by introduction of I group metals nitrates into model multibilayer membranes based onhydrated L-α-dipalmitoylphosphatidylcholine (DPPC). As it was demonstrated by means of differential scanning calorimetry, membranotropic activity of the compounds examined corresponds to certain superposition of the cation and the anion effects and, in whole, correlates with their hydration properties (kosmoropicity/chaotropoicity degrees). Thereby it was noted that IB subgroup cations systematically increased compactness of the DPPC membrane as compared to IA subgroup cations. This points to the difference in the mechanisms of the cation binding with the membranes. Analysis of FTIR spectra of the systems examined allows suggestion about two possible binding mechanisms, notably, for IA subgroup cations, it is adsoprbtion onto the DPPC membrane surface, and for IB subgroup cations, it is penetration up to hydrophilic/hydrophobic interface of the membrane. In the latter case, dehydration of the carbonyl group region takes place resulting to the membrane compaction